Weathering assessment in the Achala Batholith of the Sierra de Comechingones, Córdoba, central Argentina. I: Granite–regolith fractionation - Campodonico, Verena Agustina (2014)
Weathering assessment in a weathering-limited environment is a difficult task because a significant proportion of the regolith has been removed by tectonically-induced denudation. In such an environment, the remnants of the altered mineral debris must be studied with care in order to attain a meaningful picture of the rate and intensity of ongoing weathering. A monolithologic (i.e., granite), small (~ 2 km2), and mountainous (~ 1500 m elevation) drainage basin in the Sierras de Comechingones (31°54′07″S 64°45′28″W–31°53′11″S 64°44′16″W, Córdoba, central Argentina) was selected as a pilot area to survey the nature of weathering in a weathering-limited erosional setting, and a semiarid climatic regime. A relatively thin-layered, coarse-grained regolith and scattered sediment (i.e., fine-grained regolith) that had accumulated in valleys and topographic depressions were analyzed. The most abundantly identified clay mineral in the regolith is illite followed by kaolinite > smectite. Smectite seems to be the only clay mineral clearly associated with weathering. Petrographic observations and geochemical analyses, supported by statistical tests, define chemical weathering as incipient. Petrography indicates that plagioclase and biotite are the main mineral phases affected by alteration, which is more intense in the fine-grained regolith. Coarse- and fine-grained regoliths are chemically similar, among them and with the country rock, with statistically significant losses in the fine fraction of MgO, MnO and P2O5. Depletions of trace elements and REE, which are best explained by sorting than by actual rock alteration, are not statistically significant. Ternary diagrams reveal that the masses of Al2O3, CaO, Na2O and K2O were not significantly altered during weathering and transportation, and that regolith samples correspond to a coarse residue relatively enriched in feldspars (and quartz), where the mud-fraction (with high clay mineral contents) has been removed from the drainage basin by high-energy processes.